A Large-Scale Synthesis and Characterization of Quaternary CuInxGa1−xS2 Chalcopyrite Nanoparticles via Microwave Batch Reactions - Chivin Sun; Richard D. Westover; Gary Long; Cyril Bajracharya; Jerry D. Harris; Alex Punnoose; Rene G. Rodriguez; Joshua J. Pak (International Journal of Chemical Engineering)
Various quaternary CuInxGa1−xS2 (0≤x≤1) chalcopyrite nanoparticles have been prepared from molecular single-source precursors via microwave decomposition. We were able to control the nanoparticle size, phase, stoichiometry, and solubility. Depending on the choice of surface modifiers used, we were able to tune the solubility of the resulting nanoparticles. This method has been used to generate up to 5 g of nanoparticles and up to 150 g from multiple batch reactions with excellent reproducibility. Data from UV-Vis, photoluminescence, X-ray diffraction, TEM, DSC/TGA-MS, and ICP-OES analyses have shown high reproducibility in nanoparticle size, composition, and bandgap.